Democracy and Public Administration in Pakistan - Amna Imam; Dar, Eazaz A. (Boca Raton CRC Press, 2014)
This book explores the role of the grass roots public administrative institution of DC & DM in historical context for Pakistan, and its viability for a meaningful democracy and stability of the country. The authors contend that Pakistan's democracy to-date lacks firm foundation, as evidenced by the country's disintegration in 1971, violence and drugs in the 80s, crime infested communities in the 90s, terrorism in the 2000s, and the current volatile situation in Balochistan and FATA, as well as high crime rate and lacking sense of security among the communities of Pakistan.
Include References and Index.
Keywords: Pakistan -- Democracy -- Politics and government